Experimental and numerical evaluation of diesel-hydrogen dual-fuel combustion in a HD single cylinder engine - Monemian Esfahani, Emadoddin (2019)
Climate changes emerging in the last few decades have resulted in accelerated efforts to guarantee a viable global ecosystem. Despite the aim of low-carbon economies to integrate all aspects for the minimal GHG outputs, the transport sector is under severe obligation to abide due to the related substantial contribution of CO2 emissions. Although, in the last few years the electrification of powertrain systems has gained significant attention in the media, it is widely acknowledged by the industry that the internal combustion engine will remain a dominant source of propulsion for decades to come. In recent years, conventional fossil fuels (gasoline and diesel) have been partially replaced with the alternative fuels such as biodiesel, natural gas, ethanol, hydrogen, etc. These substitutions were beneficial in diverse perspectives making significant reductions in exhaust pollutants with maintained performance. The currently reported work was concerned with experimental and numerical evaluation of the potential to partially replace diesel with hydrogen fuel, which continues to attract attention as a potential longer term alternative fuel solution, whether produced on-board or remotely via sustainable methods. The test engine adopted was of a single cylinder HD diesel with typical common rail diesel fuel injection and EGR of a production HGV’s engine. The experimental work was involved with the fumigation of hydrogen and intake air enrichment with oxygen at two particular engine loads (6 and 12 bar net indicated mean effective pressure -IMEPn-) typically visited under real world HGV driving conditions. Highest practical hydrogen substitution ratios could increase indicated efficiency by up to 4.6% and 2.4% while reducing CO2 emissions by 58% and 32% at 6 and 12 bar IMEPn respectively. Soot and CO emissions were reduced as more hydrogen was supplied, particularly at 6bar IMEP. Furthermore, intake air enrichment with oxygen resulted in a faster combustion process. This could restraint soot and minimised CO emissions at the expense of considerably higher NOx emissions. The numerical study was made using the commercial engine simulation package, GT-Power. Initially a reverse-run calculation known as Three Pressure Analysis (TPA) was applied for determining the cylinder trapped conditions in addition to the measured burn rate. Two distinct phenomenological models were used in parallel with aim of modelling the dual-fuel combustion. By comparing the optimised calibration factors in different operating points, in-depth evaluation of the unique dual-fuel combustion phenomenon was possible, including evaluation of burning velocities and the knock-on effects on performance under varied mixture compositions. It was concluded that hydrogen substitution provides a viable method of displacing diesel and the associated carbon emissions with favourable accompanying reductions in soot. The phenomenological “DualFuel” model performed well under ‘conventional’ dual-fuel conditions but was less reliable when a proportion of the diesel was premixed. The arising error was largely associated with lack of dual-fuel burning velocity data, which will remain a key barrier to dual-fuel simulation as the premixing is largely acknowledged to improve the combustion efficiency.